Determinants of e-commerce, artificial intelligence, and agile methods in small- and medium-sized enterprises - Barata, S.; Ferreira, F.; Carayannis, E.; Ferreira, J. (IEEE Transactions on Engineering Management, 2024)
Small- and medium-sized enterprises (SMEs) are constrained by scarce resources, yet they are under strong pressure to maintain a competitive position in global markets, especially during crises such as the coronavirus disease-19 (COVID-19) pandemic. In this context, electronic commerce (hereafter e-commerce) platforms combining artificial intelligence (AI) and agile methods have been thriving. On the one hand, AI is a better way to process the data essential to platform customization and optimization. On the other hand, agile adoption ensures iterative software delivery as well as improved management practices that reduce uncertainty and allow SMEs to adapt more easily to new market requirements. A limited number of studies have covered all three topics, especially in relation to these companies. This research focused on creating an innovative model to identify determinants that favor or inhibit SME development of e-commerce, AI, and agile method projects. The model was developed using cognitive mapping—based on strategic options development and analysis—and decision-making trial and evaluation laboratory technique. Recommendations were generated to help SMEs use these tools to acquire a stronger competitive position in global markets.